Stronger associations of abdominal obesity-related triglyceride-glucose indices with type 2 diabetes compared to general obesity-related indices in community-dwelling Chinese adults: a cross-sectional study - Lu, Xiaoting; Chen, Shanshan; Wang, Cheng; Lin, Diaozhu; He, Fengyi; Lin, Xiuhong; Wu, Hongshi; Liang, Ping; Yan, Li; Ren, Meng; Chen, Chaogang (Frontiers in Endocrinology, 2025)
ObjectivesThe relationships between the triglyceride-glucose (TyG) index, TyG-related parameters of different obesity phenotypes and the risk of type 2 diabetes (T2D) remain unclear. We aimed to determine associations between TyG index, obesity-related TyG parameters and T2D risk in Chinese adults.MethodsThis cross-sectional study included 9489 participants aged ≥40 years from a large scale, community-based cohort study. Multivariable logistic regression was performed to estimate odds ratios (ORs) and 95% confidence intervals (CIs). The receiver operating characteristic (ROC) curve was employed to test and compare the predictive power of obesity-related TyG parameters across different phenotypes for the risk of T2D.ResultsA total of 2081 (21.9%) participants with T2D were identified. When comparing with participants in the bottom quartile of TyG index, a heightened risk of T2D was observed among the highest quartile group, with an adjusted OR of 5.89 (95% CI: 4.98–6.98). Comparable relationships were found between obesity-related TyG indices and T2D, including TyG-waist circumference (TyG-WC), TyG-waist-to-height ratio (TyG-WHtR), TyG-body mass index (TyG-BMI) and TyG-body fat percentage (TyG-BFP). Abdominal obesity-related TyG indices had the highest predictive capability for T2D, with the area under the curve (AUC) was 0.711 (0.697–0.724) for TyG-WHtR and 0.705 (0.691–0.719) for TyG-WC, which was superior to the general obesity-related TyG indices, with the AUC were 0.683 (0.669–0.698) and 0.631 (0.616–0.646) for TyG-BMI and TyG-BFP, respectively.ConclusionsOur findings demonstrate a positive associations between TyG index, obesity-related TyG indices and risk of T2D. Abdominal obesity-related TyG indices had a better predictive value to diabetes than general obesity-related TyG indices.